Inclusion of Milk Thistle Seed and Achyranthes japonica Extract Alone or in Combination in Diet of Weaning Pigs Results in Similar Growth Outcomes - Shanmugam Suresh Kumar; Se Yeon Jang; In Ho Kim (Life)
The objective of this study was to assess the impacts of milk thistle seed (MTS) and Achyranthes japonica extract (AJE), both individually and in combination, on growth performance, nutrient digestibility, fecal score, fecal gas emissions, and cytokine responses in n = 120 crossbred [(Landrace Yorkshire) × Duroc] weaning piglets with an initial body weight of 6.53 ± 1.24 kg. Pigs were selected based on sex and randomly assigned to one of four dietary treatments for 6 weeks. The experimental diets were as follows: (1) CON—control/basal diet; (2) AJE (CON + 0.10% AJE); (3) MTS (CON + 0.10% MTS); and (4) CMB—combo feed (CON + 0.05% of AJE + 0.05% of MTS). Each treatment consisted of six replicates with five pigs (three ♀ and two barrows ♂) per pen. The incorporation of MTS has the potential to enhance (p < 0.05) the average daily gain in weaning pigs, particularly when used alone or in combination with AJE. But there were no significant effects or adverse effects observed on other growth parameters such as body weight, average daily feed intake, and gain-to-feed ratio. Also, there were no notable changes found in nutrient digestibility, fecal score, fecal gas emissions, or cytokine production. In summary, MTS and AJE, administered alone or in combination, reveal similar growth outcomes, suggesting that both additives could serve as potential options to improve animal performance without adverse effects.